2020
DOI: 10.1186/s12879-020-05444-2
|View full text |Cite|
|
Sign up to set email alerts
|

Differential susceptibility of Onchocerca volvulus microfilaria to ivermectin in two areas of contrasting history of mass drug administration in Cameroon: relevance of microscopy and molecular techniques for the monitoring of skin microfilarial repopulation within six months of direct observed treatment

Abstract: Background Ivermectin is an excellent microfilaricide against Onchocerca volvulus. However, in some regions, long term use of ivermectin has resulted in sub-optimal responses to the treatment. More data to properly document the phenomenon in various contexts of ivermectin mass drug administration (IVM-MDA) is needed. Also, there is a need to accurately monitor a possible repopulation of skin by microfilariae following treatment. Skin snip microscopy is known to have a low sensitivity in individ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Following treatment with ivermectin, skin repopulation by O. volvulus mf has been shown to slowly resume within 3 to 6 months, but not reaching the initial infection intensity [ 35 , 36 ]. Additionally, previous research in endemic communities in Cameroon has suggested that in villages with > 20 years of CDTI as is the case with our study sites, there is a lower mf clearance and higher repopulation rate after treatment with ivermectin [ 37 ]. One can reasonably argue that, despite the sub-optimal coverage, the ivermectin treatment had lowered the community microfilarial load in the study villages such that the probability of a black fly taking up mf during a blood meal would also be low.…”
Section: Discussionsupporting
confidence: 59%
“…Following treatment with ivermectin, skin repopulation by O. volvulus mf has been shown to slowly resume within 3 to 6 months, but not reaching the initial infection intensity [ 35 , 36 ]. Additionally, previous research in endemic communities in Cameroon has suggested that in villages with > 20 years of CDTI as is the case with our study sites, there is a lower mf clearance and higher repopulation rate after treatment with ivermectin [ 37 ]. One can reasonably argue that, despite the sub-optimal coverage, the ivermectin treatment had lowered the community microfilarial load in the study villages such that the probability of a black fly taking up mf during a blood meal would also be low.…”
Section: Discussionsupporting
confidence: 59%
“…This will allow for faster decision making without the need for a second-stage mapping with larger samples sizes and the associated financial and logistical costs. We will test this hypothesis and establish an initial cutoff, with the aid of modeling, using urine from an upcoming study funded by COR-NTD that will compare O-150 serology to the O-150 LAMP assay [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, program fatigue in MDA has been reported after years of implementation, and an individual in an endemic area may find repeated MDA inconvenient or lose confidence in the MDA campaign. Furthermore, alarming reports of reduced drug efficacy in Ghana and Cameroon may also signal the development of resistance [18,19]. This situation, coupled with the risk of ivermectin resistance, presents an urgent need for a novel anthelmintic drug that preferably possesses macrofilaricidal or permanent sterilizing activity.…”
Section: Elimination Of Onchocerciasis-current Status and The Need For Novel Treatment Strategiesmentioning
confidence: 99%